(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
This article aims at mapping and analyzing the ever increasing recourse by Italian public administration to AI systems. It focuses on three different types of administrations: independent authorities, smart cities and central administrations. For each group of administrations, it asks through which proceedings a decision concerning the use of AI systems is taken, which AI systems are in the process of being experimented and for which purposes, who controls the functioning of the AI. Particular attention is paid to administrative practices and legal and institutional reality.